N-Acetylated Gemini Surfactants: Synthesis, Surface-Active Properties, Antifungal Activity, and Ecotoxicity Bioassays - Machuca, Laura Marcela (2015)
A series of N-acetylated cationic gemini surfactants (3a-e) having dimeric structures derived from tertiary amines were synthesized. Their antifungal potency and surface properties were determined. It also studied the acute toxicity of the molecule with the best performance and the best water solubility (3e) through Chlorella vulgaris and Daphnia magna bioassays. The results were compared to those obtained for a commercially available reference compound 2-(thiocyanomethylthio) benzothiazole (TCMTB). Parameters such as surface tension (γCMC), critical micelle concentration (CMC), surface excess concentration (Γ), and area per molecule (A) were determined. The resulting values indicated that the five gemini surfactants are characterized by good surface-active and self-aggregation properties. All surfactants were tested to evaluate their antifungal activity. Six fungal strains were used to conduct the study. The minimum inhibitory concentration (MIC) value was measured by the fungal growth inhibition. The results of the MICs were compared with two commercially available reference compounds (Fluconazole and TCMTB). The least active molecule was 3e, but 3b and 3d were found to be the most potent compounds with a similar activity for all strains. Candida albicans was the most sensitive one. In contrast, Aspergillus niger was resistant. Ecotoxicity of gemini 3e was assessed: the commercial formulation (TCMTB) was between three and four orders of magnitude more toxic than the gemini one for the biological species tested.